Heparins Sourced From Bovine and Porcine Mucosa Gain Exclusive Monographs in the Brazilian Pharmacopeia - Vilanova, Eduardo; Vairo, Bruno C.; Oliveira, Stephan-Nicollas M. C. G.; Glauser, Bianca F.; Capillé, Nina V.; Santos, Gustavo R. C.; Tovar, Ana M. F.; Pereira, Mariana S.; Mourão, Paulo A. S. (Frontiers in Medicine, 2019)
Most of the unfractionated heparin (UFH) consumed worldwide is manufactured using porcine mucosa as raw material (HPI); however, some countries also employ products sourced from bovine mucosa (HBI) as interchangeable versions of the gold standard HPI. Although accounted as a single UFH, HBI and HPI have contrasting anticoagulant activities (~100 and ~200 IU mg-1, respectively) because of their compositional differences. The concomitant use of HBI and HPI in Brazil has already provoked serious bleeding incidents, which lead to the withdrawn of HBI products in 2009. In 2010, the Brazilian Pharmacopeia (BP) formed a special committee to develop two complementary monographs approaching HBI and HPI separately, as distinct active pharmaceutical ingredients (APIs). The committee rapidly agreed on requirements concerning composition and presence of contaminants based on nuclear magnetic resonance and anion-exchange chromatography. On the other hand, agreements on the anticoagulant activity of HBI were subject of long and intense disputes. Nevertheless, the committee ultimately agreed to recommend minimum anti-FIIa activities of 100 IU mg-1 for HBI and 180 IU mg-1 for HPI. Upon the approval by the Brazilian Health Authority (ANVISA), the BP finally published the new monographs for HBI and HPI APIs along the years of 2016 and 2017. These pioneer monographs consist in a pivotal step toward a safest use of HBI and HPI as interchangeable anticoagulants and a valuable template for the reformulation of pharmacopeias of other countries willing to introduce HBI.